2003
DOI: 10.1007/s00464-002-9069-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open appendectomy

Abstract: Laparoscopic appendectomy is as safe and effective as the open procedure. It significantly reduces the rate of postoperative wound infection. However, it is still acceptable to perform the open procedure, especially in hospitals without a large amount of laparoscopic experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…The male-to-female ratio of the laparoscopic group was 2.4:1 and mean age group was 23 years while the OA group male-to-female ratio was 2.3:1 with a mean age of 20.2 years. 9 Average age groups in Al-Bassam, and Nassir et al studies were 8 and 28 years, respectively, allowing this study to cover wider range of age groups and associated findings in each research. 7,8 Mean operative time (min) in the laparoscopic procedures was 67.3±25.1 for LA and 59.4±11.2 for OA procedures in Marzouk et al study while in Al-Bassam study, which data is on laparoscopic appendectomy in children, the mean operative time was 53±24.41 for uncomplicated appendicitis and 63.5±17.33 for complicated appendicitis and it was about 80 mins in Nassir et al study, whose study group underwent laparoscopic appendectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The male-to-female ratio of the laparoscopic group was 2.4:1 and mean age group was 23 years while the OA group male-to-female ratio was 2.3:1 with a mean age of 20.2 years. 9 Average age groups in Al-Bassam, and Nassir et al studies were 8 and 28 years, respectively, allowing this study to cover wider range of age groups and associated findings in each research. 7,8 Mean operative time (min) in the laparoscopic procedures was 67.3±25.1 for LA and 59.4±11.2 for OA procedures in Marzouk et al study while in Al-Bassam study, which data is on laparoscopic appendectomy in children, the mean operative time was 53±24.41 for uncomplicated appendicitis and 63.5±17.33 for complicated appendicitis and it was about 80 mins in Nassir et al study, whose study group underwent laparoscopic appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Concluding that this might indicate higher rate of intra-abdominal infections in the LA patients than OA ones, while wound infections are mainly shown in OA cases. 9 Al-Bassam has found that there were no cases of wound infection and intra-abdominal collections in the uncomplicated appendicitis LA procedures while 13% of the complicated appendicitis suffered wound infections and intra-abdominal collections. 8 In Nassir et al study, 5.35% suffered postoperative wound infections, along with 3.70% suffering intra-abdominal abscesses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13][14][15] Advantages of LA include reduced postoperative pain and cosmesis. 8,12,[14][15][16][17][18][19][20][21] Despite the popularity of LA, it is still a controversial subject and some studies demonstrate a preference towards OA.…”
Section: Introductionmentioning
confidence: 99%